The Sick Placenta—The Role of Malaria - Brabin, B.J.; Romagosa, C.; Abdelgalil, S.; Menéndez, C.; Verhoeff, F.H.; McGready, R.; Fletcher, K.A.; Owens, S.; d'Alessandro, U.; Nosten, F.; Fischer, P.R.; Ordi, J. (Placenta (Eastbourne), 2004)
The human placenta is an ideal site for the accumulation of Plasmodium falciparum malaria parasites, and as a consequence serious health problems arise for the mother and her baby. The pathogenesis of placental malaria is only partially understood, but it is clear that it leads to a distinct epidemiological pattern of malaria during pregnancy. The objectives of this review are: (1) To review recent data on the epidemiology of malaria in pregnancy, with emphasis on placental malaria; (2) to describe the pathological changes and immunological factors related to placental malaria; and (3) to discuss briefly the functional consequences of this infection for the mother and her baby. The review attempts to bring together local events at the maternal-fetal interface which encompass immunological and pathological processes which relate to the epidemiological pattern of malaria in pregnancy in areas of both high and low malaria transmission. An integrated understanding of the epidemiological, immunological and pathological processes must be achieved in order to understand how to control malaria in pregnancy. The yearly exposure of at least 50 million pregnancies to malaria infection makes it the commonest and most recurrent parasitic infection directly affecting the placenta. These statistics and our limited understanding of its pathogenesis suggest the research priorities on this subject.